Study Of Consumer Acceptance On Patin Fish (Pangasius hypophthalmus) Nugget With Substitution Of Jackfruit Seed Flour (Artocarpus heterophyllus lamk) - Darwin Suar Bhekti; Dewita Dewita; Suparmi Suparmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2020)
ABSTRACT Thisresearchwas intended to determine the effect of substitution of jackfruit seed flour on the patinfish nugget products towards consumer acceptance measured by organoleptic test (appearance, texture, odor, and flavor) and proximate analysis (moisture, fat, and protein).The method used in thisresearchwas an experimental method and the experimental design usedwas a Completely Randomized Design (CRD) with 4 treatments i.e.B0 (without jackfruit seed flour substitution), B1 (50 g jackfruit seed flour substitution), B2 (100 g jackfruit seed flour substitution), B3 (150 g jackfruit seed flour substitution).Based on the results of this research showed that B1(50 g jackfruit seed flour substitution) wasthe best treatments refers to organoleptic value with the appearance criteria was light brown 3.70, the odor criteria was typical fish odor 3.40, the flavor criteria was savory taste 3.31, and the texture criteria was compact texture 3.06. While the proximate analysis of B1was 13.04%protein content, 9.35%fat content and 62.57% moisture content.Keywords: Nugget,Jackfruit seed flour,Pangasius hypophthalmus.,